Validity and Reliability Study of the Turkish Form of the Family Support Scale for the Older People - Tuğba Solmaz; Tuba Korkmaz Aslan (AVES, 2024)
Aim: The Family Support Scale is a used scale to assess family support in older people. The purpose of this study was to test the Family Support Scale for older people in Turkish and to examine its validity and reliability. Methods: This was a methodological study. This study sample enrolled 250 older individuals. The study was conducted between July-December 2022. In data collection, sociodemographic information form and The Family Support scale were used. The inclusion criteria for this study selected participants who were 65 years or older, literate, open to communication, living with at least one family member, and who volunteered to participate in the research. In the study, who developed the original scale, was contacted via e-mail and the necessary permission was obtained for the Turkish validity and reliability of the scale. Language equivalence, content validity, exploratory factor analysis, and confirmatory factor analysis of the scale were performed. Internal consistency and total item score correlation were calculated to ensure validity and reliability. Results: The scale is compatible in terms of language and content suitability, CVI (Language)= 0.87; CVI (Content)=0.099. In the validity analyzes of the scale; the factor loadings values of the scale were found to be between 0.36 and 0.83, and the explained variance (54.78%) was at a sufficient level according to the EFA results. It was determined that factor loading values for all items were varied between 0.58 and 0.97 and factor load values were statistically significant in CFA (p<.05). It was determined that the fit indices were RMSEA=0.064, GFI=0.99, CFI=0.99, NFI=0.99, x2/df=2.03 at the desired level. In the reliability analysis, it was found that the internal consistency coefficient (α: 0.94) was quite reliable, and the total correlation values of the scale ranged between 0.48 and 0.83. Conclusion: The cross-cultural adaptation of this scale has been realized successfully in Turkish. Health care providers may utilize this tool to evaluate family support for older people.